Representasi Emosi Dalam Komunikasi Interpersonal melalui Musik Video Dunia Tipu-Tipu - Syahida, Santia Indah; Mardiana, Lisa (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Emotional expression is a form of nonverbal communication that can strengthen meaning in interpersonal relationships. This study aims to examine the representation of emotional expressions in interpersonal communication in the music video "Dunia Tipu-Tipu" by Yura Yunita. This research uses an interpretative qualitative approach with the Roland Barthes semiotic analysis method. The music video "Dunia Tipu-Tipu" displays various forms of emotional expressions without dialog, through visual symbols such as eye gaze, facial expressions, and body gestures. The emotions depicted in a number of scenes show the dynamics of relationships between individuals, including couples, friends, and families. The results show that expressions such as sadness, affection, hope, and gratitude are deeply displayed through nonverbal communication. All of these representations are analyzed based on the three layers of meaning in Barthes' semiotics, namely denotation, connotation, and myth. The findings show that visual symbols in music videos are able to convey strong emotional messages and shape cultural constructions of honest and authentic interpersonal relationships.